Pemberian Vitamin Sebagai Penanganan (Avitaminosis) Pada Sapi Di Kecamatan Selong Dan Kecamatan Suela - Tapaul Rozi; Muh. Robby Gunansyah Putra; Ahyar Hamdani; muhammad bazil habibullah; Muhammad Barzil Habibullah; Ira Nabila; Olivia Hayatunnupus (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service activity aims to assess the effectiveness of vitamin administration as a treatment for avitaminosis in cattle in Selong and Suela Districts. The main problem found in the field is the persistence of vitamin deficiency cases in cattle due to suboptimal feed management and continued reliance on forage without additional supplementation. The methods used in this activity included observation, physical examination of the cattle, and treatment measures through the administration of vitamin B12 and vitamin B complex via intramuscular injection. A total of 25 cattle were treated, consisting of 10 in Selong District and 15 in Suela District. The results of the activity showed that vitamin administration was able to provide a relatively rapid recovery response, characterized by increased appetite, activity, and physical condition of the cattle within 2–3 days after the treatment. Scientifically, this is related to the role of vitamins as coenzymes in energy metabolism and improving the livestock's immune system. Based on these results, it can be concluded that vitamin administration via injection is an effective method in treating avitaminosis in cattle, especially in traditional livestock systems. However, this effort needs to be accompanied by improvements in feed management and increased farmer knowledge to prevent similar incidents in the future.